(untitled) (Journal of the College of Basic Education, 2022)
In response to the fact that most of residential buildings in Middle East region designed far away to be effectively efficient, and also the fact that a significant amount of the energy produced within these countries is consumed by the buildings, this research trying to develop standards can be used in the future on residential buildings for this region from energy point of view, with additional suggestions for other optimization measure may overall efficiency, finally, the payback period of the project to be reduced. This study aims to identify an appropriate solar driven cooling system configuration and size with respect to fulfill target values in primary energy savings, solar thermal system exploitation and economics. This paper presents two different techniques to design an efficient building able to comply with different climate conditions in IRAQ. In the first technique, the research focusing on estimating the Energy demand of a reference building by using advanced simulation tools. The second technique proposed to simulate an absorption machine solar thermal driven, which can be used with HVAC system to cover the cooling load during summer period by using dynamic modeling tool.